Calamity café - Leeson, Gayle, 1967- (Leeson, Gayle, 1967- Down South Café mystery., 2016)
Aspiring chef Amy Flowers is ready to open her own café offering old-fashioned Southern food. But her dream may go up in smoke when someone kills the competition.